Studi Kelayakan Pembangunan Pabrik Baterai Sepeda Motor Listrik di Kawasan Jiipe, Kabupaten Gresik, Jawa Timur Oleh PT “X” - Oetomo, Dedy Setyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
in the future Indonesia will become a battery producer for electric vehicles in the world with one abundant main ingredient, namely nickel. PT "X" is a company that will be engaged in the production of electric vehicle batteries, especially for electric motorbikes, the product produced is an electric battery with a power capacity of 8 kWh and plans to build its industry in the JIIPE Gresik area, with a production capacity of 48,216 units or 385,728 kWh. With a total investment cost of Rp. 118,224,586,566, -, of which 70% is financing with loans to bank financial institutions. From the results of the financial feasibility analysis, an IRR value of 44% was obtained with an NPV value of Rp. 984,601,222, and the return on investment is 3 years, and according to the criteria above, the EV motor battery factory construction project can proceed to the next stage